The Disabled Children: Is It Important for Them to Participate in Sport and Physical Education Program? - Nurhayati, (Ordik, 2008)
One problem that the Indonesian government has had recently is the growth of number of people with disabilities caused by accident, poor nutrition, or natural disaster.  They need special assistance to overcome their physical problems, so they wont depend on other to deal with their daily activities.  Some researches show that sport and physical education program are useful tools for disabled to get healthy development.  However, there are some problems that the disabled have when they participate in sport and physical education program.  This writing tries to find out these major problems, causes of the problems and the the possible solutions for the problems.